Effects of an 8-day field training on body composition, serum hormone concentrations and maximal force production in military conscripts - Savolainen, Sini (2015)
Savolainen, S. 2015. Effects of an 8-day field training on body composition, serum hormone concentrations and maximal force production in military conscripts, 64p. University of Jyväskylä. Department of Biology of Physical Activity. Science of Sports Coaching and Fitness Testing. The aim of this study was to examine physiological consequences on 8-day strenuous military field exercise. 26 men (20 ± 1 yrs, 53,7 ± 4,5ml/kg/min, 178,4 ± 7,2cm, 71,2 ± 7,2kg) in the end of their military service participated in the study. The research data was collected in five testing day (pre1, pre2, middle, post and follow-up); body composition, physical performance and basal blood levels were measured. The changes in body composition were calculated with the information from total body water measurements with deuterium dilution techique. Serum hormones analysed from the basal blood were total testosterone and cortisol and carrier protein SHBG. Bilateral isometric leg and arm extension force were used to describe physical performance. RESULTS: Total body mass decreased by 1.8±1kg (p<0.001) during the 8-day field exercise. Fat mass absolute decrease was 2.0±1kg (p<0.001) and a relative change was -18.7±13 %. The absolute change in total fat percentage was -2.4±2% (p<0.001). Maximum voluntary contraction decreased during the field exercise in bench press and regained in the end of the field exercise; 761±131 N (pre1); 758±127 N (pre2); 676±137 N (middle, p<0.001); 727±117 N (post, p<0.05) measurements. Relative change between pre2 and middle measurements is 11%. Maximum voluntary contraction decreased in leg press also and regained in the end of field exercise; 2560±512 N (pre1); 2592±520 N (pre2); 2401±584 N (middle, p<0.01); 2499±541 N (post, p<0.01). Relative change in maximum voluntary contraction between pre2 and middle measurements is 7%. Significances compared to pre2 measurement. Maximal rate of force development in the bench press was 24492±12919 N/s (pre1); 22865±13253 N/s (pre2); 15564±7397 N/s (middle, p<0.01); 15942±7276 N/s (post p<0.01). Maximal rate of force development in the leg press was 28767±8570 N/s (pre1); 25119±8945 N/s (pre2); 16684±7404 N/s (middle, p<0.001); 16720±7362 N/s (post p<0.001). Significances compared to pre2 measurement. The changes in physical performance did not relate with the energy balance. Plasma serum cortisol (from 498 to 648nmol/L) and SHBG (from 37.1 to 41.3nmol/L) concentrations increased significantly (p<0.001) and serum total testosterone (from 21.1 to 14.9nmol/L) decreased significantly (p<0.001) in the middle measurements compared to pre 2 measurements. In the post measurements the cortisol was normalized on the pre2 levels. Testosterone regained slightly from middle to post measurement (p<0.001) but it still differed significantly from pre 2 measurement. The SHBG concentration increased more after the middle measurement, post and follow measurement levels differed significantly compared to middle measurement (p<0.001). In testo/cortisol-ratio there was a significant decrement in the middle measurement compared to pre 2 measurement (p<0.001). Testo/SHBG-ratio decreased significantly in middle and post measurements compared to pre 2 measurement (both p<0.001). IN CONCLUSION: High physical loading and sleep deprivation or lack of rest was enough strenuous to affect the physical performance during the field exercise. Maintenance in muscular strength may be facilitated by the energy balance and adequate sleep.